The impact of movement control order during the COVID-19 pandemic on lifestyle behaviours and body weight changes: findings from the MYNUTRILIFECOVID-19 online survey - Chin, Yit Siew; Woon, Fui Chee; Chan, Yoke Mun (Public Library of Science, 2022)
Background: The COVID-19 pandemic lockdowns have affected daily lives of the communities worldwide. This study aims to determine the lifestyle behaviours and their associations with body weight changes among Malaysian adults during the Movement Control Order (MCO) due to COVID-19 pandemic. Methods: A total of 1319 Malaysian adults participated in this cross-sectional online survey. Information on anthropometric data including body weight and height, and lifestyle behaviours including eating pattern, physical activity, and sleep pattern were self-reported by the respondents. A multivariable generalised linear mixed model was used to assess the associations between lifestyle behaviours and body weight changes with adjustment of confounding factors; namely, age, sex, ethnicity, and body weight status before MCO. Results: During MCO, 41.2% of the respondents perceived that their eating patterns were healthier, but 36.3% reduced their physical activities, and 25.7% had a poorer sleep quality. Further, the proportion of adults who reported having lose weight (32.2%) was almost similar to those who reported having gained weight (30.7%). Lifestyle behaviours including less frequent practice of healthy cooking methods and lunch skipping were associated with weight gain, while less frequent consumption of high fat foods, more frequent physical activity, and good sleep latency were associated with lower risk of weight gain. In contrast, practicing healthy eating concept, skipped lunch, and more frequent physical activity were significantly associated with weight loss. Conclusion Lifestyle behaviours were associated with body weight changes during MCO. While the COVID-19 pandemic lockdown is necessary to prevent further spread of the disease, promoting healthy lifestyle practices during lockdown should be implemented for a healthy weight and better health.